Safety analysis of foods of animal origin - Nollet, Leo M. L., 1948-; Toldrá, Fidel (CRC Press, 2011)
This book is divided into three parts: meat, processed meats, and poultry; fish and seafood products; milk and dairy products. Each of the chapters is dedicated to a specific spoilage, foodborne pathogen, parasite, virus, adulteration, residue, or toxin. Each starts with a discussion of the parameter in question. Sample preparation and cleanup methods are then reviewed in depth, followed by a detailed evaluation of various separation and detection methods. Special attention is given to explain current limits of detection and reliability. Finally, a brief summary covers the presence of these parameters in different end products, regions, and countries.
Keywords: Meat inspection.; Meat -- Analysis.; Dairy inspection.; Dairy products -- Analysis.; elektronické knihy; electronic books